Produção de zangões de abelhas africanizadas apis mellifera l. No semiárido nordestino do brasil - Araujo Neto, Edgar Rodrigues de (2019)
The main objective of this work was to test induction methods for the production of drone cells in Africanized honey bees (Apis mellifera L.) and to evaluate the factors that interfere in the production of drones during the harvest and off-season periods in the Brazilian northeastern semi - arid region. The experiments were carried out at the Technological Center of Apiculture and Meliponiculture of Rio Grande do Norte (CETAPIS), located at the Experimental Farm belonging to the Federal Rural Semi-Arid University (UFERSA) geographically defined by coordinates 5º03'37 "South Latitude and 37º23 ' 50 "west longitude, with an average altitude of 72 meters and semi-arid climate. The two methods of induction for the production of drone cells tested in the present work were: Addition of a frame containing a complete sheet of wax with workers' alveoli on the sides of the colonies (second frame) and Addition of a frame with 20 cm x 7cm of wax with alveoli of workers on the sides of the colonies (eighth frame).In addition to the methods, it was verified the effect of colony population size on the production of new combs containing drone cells in the harvest and off season, the characterization of climatic seasonality, allowing the delimitation of two periods (Harvest and Entressafra) and demonstrating the period of natural presence of drones, the morphometry of africanized honey bees' drones in a semi-arid climate region and the comparison between the construction of drone cells on both sides of the frames. The result of the induction methods was that the addition of a frame with 20 cm x 7 cm tapes of honeycomb wax was more efficient than the addition of a frame containing a complete sheet of wax with workers' alveoli on the sides of the colonies (p <0 , 05) in the harvest period, however, both methods were inefficient in the off season. Regarding the association of colony size, it was observed that the size had no influence on both the harvest and the off season. The climatic seasonality was determinant in the production of drones, where the rainy period presented a very significant difference (p <0.0001), with its peaks in the months of June and July. The morphometric evaluations of Africanized honey bee drones (Apis mellifera L.) presented mean results of 6.37 mm (± 0.97) for abdomen length, 13.06 mm (± 1.8) for total length and mean weight of 128 mg. It was possible to verify that both sides of the frame are practically mirrors, where they have almost the same number of cells, not presenting statistical difference between them